Post-intervention outcomes in farmer's behaviour and crop diversification in Chapainawabganj, Bangladesh - Nandi, Ravi; Hossain, Md. Khaled; Anupama Islam Nisho; Md Saiful Islam; Alanuzzaman Kurishi, A.S.M.; Sumona Shahrin; Mustafa Kamrul Hasan; Md. Arifur Rahaman; Krupnik, Timothy J. (TAFSSA, 2024)
Crop production is predominantly rice-centric in Bangladesh and, although economically rational, is risky and arguably unsustainable (1). In response, crop diversification emerged as an important strategy for achieving sustainable agriculture in Bangladesh (2). On-farm trials evaluated new cropping patterns in the Chapainawabganj district and promoted crop diversification among smallholder farmers. This brief summarizes the results from post-intervention outcomes in farmer behavior, covering a) preferred cropping patterns among farmers, b) perceived benefits, challenges, and transaction costs of crop diversification, and c) market awareness among trial farmers. Data were collected through face-to-face surveys involving on-farm trail farmers in the Chapainawabganj district.